2000
DOI: 10.1103/physreve.61.1743
|View full text |Cite
|
Sign up to set email alerts
|

Glass transitions and dynamics in thin polymer films: Dielectric relaxation of thin films of polystyrene

Abstract: The glass transition temperature Tg and the temperature Tα corresponding to the peak in the dielectric loss due to the α-process have been simultaneously determined as functions of film thickness d through dielectric measurements for polystyrene thin films supported on glass substrate. The dielectric loss peaks have also been investigated as functions of frequency for a given temperature. A decrease in Tg was observed with decreasing film thickness, while Tα was found to remain almost constant for d > dc and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

52
449
5
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(507 citation statements)
references
References 37 publications
52
449
5
1
Order By: Relevance
“…16 A series of polystyrene (PS) films of thicknesses between 10 and 200 nm were prepared on silicon wafers and reductions in T g for films with thicknesses less than 40 nm were measured. Results obtained for PS films on a variety of substrates using numerous experimental techniques such as ellipsometry, 16,17 dielectric spectroscopy, 18,19 X-ray reflectivity, 20 local thermal analysis 21 and probe fluorescence intensity measurements 22,23 show a consistent decrease in T g with decreasing film thickness. However, a modest increase in T g was observed with decreasing film thickness for PMMA films on silicon oxide, demonstrating the importance of polymersubstrate interactions on the measured T g .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 A series of polystyrene (PS) films of thicknesses between 10 and 200 nm were prepared on silicon wafers and reductions in T g for films with thicknesses less than 40 nm were measured. Results obtained for PS films on a variety of substrates using numerous experimental techniques such as ellipsometry, 16,17 dielectric spectroscopy, 18,19 X-ray reflectivity, 20 local thermal analysis 21 and probe fluorescence intensity measurements 22,23 show a consistent decrease in T g with decreasing film thickness. However, a modest increase in T g was observed with decreasing film thickness for PMMA films on silicon oxide, demonstrating the importance of polymersubstrate interactions on the measured T g .…”
Section: Introductionmentioning
confidence: 99%
“…These differences have implications for the properties of such materials confined on the nanometer length scale. For example, the glass transition temperature (T g ) of amorphous polymer thin films has been observed either to increase or decrease with decreasing film thickness, [16][17][18][19][20][21][22][23][24][25][26][27][28] phenomena that have attracted great interest in recent years as part of a larger effort to understand the nature of the glass transition itself. The first systematic study of the dependence of the T g on film thickness in thin polymer films was performed by Keddie et al using ellipsometry.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the investigated liquid, the realization of the confinement and even the experimental method, there is a great variety in experimental findings. Some give evidence for an accelerated dynamics in confinement [21,25,26,29,30,36], i.e. the glass transition temperature T g goes down, while others see an increase of T g [24,37,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…One large class of experiments are done on molecular liquids (such as salol, glycol, ortho-terphenyl) confined to porous material such as Vycor glass, sol-gel glass and zeolithes with pore sizes ranging from several hundred to only a few nanometer. Typical experimental methods are differential scanning calorimetry (DSC) [21,22,23], dielectric spectroscopy [24,25,26,27,28,29], neutron scattering [30,31], solvation dynamics [32,33,34] and many more.…”
Section: Introductionmentioning
confidence: 99%
“…14 Dielectric investigations of thin films supported on aluminum substrates have shown that the full width at half maximum of dielectric loss increases with decreasing thickness, suggesting that a decrease in T g is directly related to the broadening of the a-relaxation peak. 15,16 Ellipsometric measurement of thermal expansivity in supported polystyrene (PS) thin films has shown that the upper extreme of glass transition, T + , remains at a point close to the bulk T g , whereas the lower extreme, T À , continuously decreases with decreasing film thickness, suggesting a broadening of glass transition in films thinner than 30 nm. 17 However, such a broadening has not been observed in free-standing films.…”
Section: Introductionmentioning
confidence: 99%